Policing Social Marginality: Contrasting Approaches. Issue 4 (10th February 2017) - Herbert, Steve; Beckett, Katherine; Stuart, Forrest
Abstract : Urban police officers concentrate much attention on individuals who experience various forms of inequality. Some police tactics that address the socially marginal garner public concern, especially when violence occurs. Solutions to such police‐community tensions are elusive, in part because police cannot meaningfully reduce inequality. Yet there are better and worse ways to police the impoverished, and we use this article to contrast three general approaches: aggressive patrol, coercive benevolence, and officer‐assisted harm reduction. We contrast their operating logics and their implications for police practice and tactics. We find great merit in officer‐assisted harm reduction, which is a nascent effort. Pioneered in Seattle, it helps to reorient police culture and practice and enables efforts to address some of the challenges facing many impoverished individuals. Although its widespread adoption will not eliminate police‐community tension in poor communities, it is superior to other alternatives, and thus deserves replication.